Anti-diabetic potential of Sapium ellipticum (Hochst) Pax leaf extract in Streptozotocin(STZ)-induced diabetic Wistar rats - Osasenaga Macdonald Ighodaro; Oluseyi Adeboye Akinloye (BMC, 2017)
Abstract Backgound Ethnobatanical survey associates Sapium ellipticum (SE) with antidiabetic usage among other medicinal functions in different parts of Africa. More importantly, previous studies on the plant extract in our laboratory showed that SE has significant effects on the activities of carbohydrate metabolizing enzymes such as glucokinase, glucose-6-phosphatase, α-amylase and α-glucosidase. In view of these, the anti-diabetic potential of the plant leaf extract in streptozotocin (STZ)-induced diabetes rat model (Wistar strain) was examined. Methods Diabetes was induced in experimental animals via single intraperitoneal dose (55 mg/kg BW) of freshly prepared STZ. SE was evaluated at 400 and 800 mg kg−1 of body weight (BW), against metformin (12 mgkg−1 BW). Treatments were done orally (p.o), twice daily at 8 h interval for a period of 21 days. Results SE significantly reduced fasting blood glucose (FBG) level by 46.5 and 44.4% (400 and 800 mg dosage respectively) compared to initial diabetic values. However, the effects were significantly lower than 72.6% glucose reduction produced by metformin. Hepatic and skeletal muscle glycogens were observed to increase by 27.06 and 12.55% respectively in SE-treated rats (800 mg dosage) compared to their corresponding values in diabetic control animals. Plasma and pancreatic insulin contents were also improved (31.77 and 52.34% respectively) by SE administration. The histopathological examination of the pancreas indicates beta cells regeneration in the treated animals, particularly in diabetic rats treated with 800 mg dosage of the extract compared to the diabetic control animals and metformin group. The presence of phenolic compounds namely amentoflavone, lupeol and luteolin-7-O-glucoside in SE as characterized and reported in our previous study is likely responsibly for the antidiabetic effects of the plant extract noted in the present study. Conclusion The outcome of this study provides scientific basis in support of the medicinal relevance of SE and lend credence to its utilization in folk medicine for the treatment of diabetes and other oxidative stress-related ailments.